Xanthatin mediates G2/M cell cycle arrest, autophagy and apoptosis via ROS/XIAP signaling in human colon cancer cells. Issue 18 (16th September 2020) - Geng, Ya-di; Zhang, Lei; Wang, Guo-Yu; Feng, Xiao-Jun; Chen, Zhao-Lin; Jiang, Ling; Shen, Ai-Zong
Abstract: Xanthatin is a natural plant bicyclic sesquiterpene lactone extracted from Xanthium plants (Asteraceae). In the present study, we demonstrated for the first time that Xanthatin inhibited cell proliferation and mediated G2 /M phase arrest in human colon cancer cells. Xanthatin also activated caspase and mediated apoptosis in these cells. Concomitantly, Xanthatin triggered cell autophagic response. We found down-regulation of X-linked inhibitor of apoptosis protein (XIAP) contribute to the induction of apoptosis and autophagy. Moreover, reactive oxygen species (ROS) production was triggered upon exposure to Xanthatin in colon cancer cells. ROS inhibitor N-acetylcysteine (NAC) significantly reversed Xanthatin-mediated XIAP down-regulation, G2 /M phase arrest, apoptosis and autophagosome accumulation. In summary, our findings demonstrated that Xanthatin caused G2 /M phase arrest and mediated apoptosis and autophagy through ROS/XIAP in human colon cancer cells. We provided molecular bases for developing Xanthatin as a promising antitumor candidate for colon cancer therapy. Abbreviations: ROS reactive oxygen species DMSO dimethyl sulfoxide 5-FU 5-Fluorouracil 3-MA 3-Methyladenine DCFH-DA 2'7'-dichlorfluorescein-diacetate NAC N-acetylcysteine XIAP X-linked inhibitor of apoptosis protein Abstract :